Development of a reliable low cost six-pulse generator for power electronics laboratory works in Universiti Tenaga Nasional - Azau M.A.M.; Jaafar S.; Meng T.G. (Institute of Electrical and Electronics Engineers Inc., 2023)
This research aims to develop a low cost six-pulse generator prototype that can be used as a teaching purpose for Power Electronics Laboratory subject offered in Universiti Tenaga Nasional. The proposed low cost device should be able to produce the same results and performs as good as the commercial six-pulse generators. The existing six-pulse generators used in the Power Electronics Laboratory costs about MYR 2000 and it has to be purchased in a package which may cost tenth of thousands Malaysian ringgit. Currently there are six units of the six-pulse generators, 3 of which are reserved as standby units to replace any malfunction devices. Therefore the students are grouped in five and they need to share the device. This will lead to an imbalance learning process where slow students may not take part in the laboratory experimental works. By developing this low cost six-pulse generator, more students can have access to the device and get involved during the experimental works. The device is developed on a flexible platform environment which compatible with the rest of the hardware in the workbench and it allows the designers/students to explore the usage through software expansion or development. Since its components are easily purchased from local electronics stores, this device is easily maintained and requires less repair time compared to the existing six-pulse generator. © 2013 IEEE.